Siderophore-Microcins in Escherichia coli: Determinants of Digestive Colonization, the First Step Toward Virulence - Massip, Clémence; Oswald, Eric (Frontiers in Cellular and Infection Microbiology, 2020)
Siderophore-microcins are antimicrobial peptides produced by enterobacteria, especially Escherichia coli and Klebsiella pneumoniae strains. The antibiotic peptide is post-translationally modified by the linkage of a siderophore moiety. Therefore, it can enter and kill phylogenetically related bacteria by a “Trojan Horse” stratagem, by mimicking the iron-siderophore complexes. Consequently, these antimicrobial peptides are key determinants of bacterial competition within the intestinal niche, which is the reservoir for pathogenic E. coli. The most frequent extraintestinal infections caused by E. coli are urinary tract infections. Uropathogenic E. coli (UPEC) can produce many virulence factors, including siderophore-microcins. Siderophore-microcins are chromosomally encoded by small genomic islands that exhibit conserved organization. In UPEC, the siderophore-microcins gene clusters and biosynthetic pathways differ from the “archetypal” models described in fecal strains. The gene cluster is shorter. Thus, active siderophore-microcins production requires proteins from two other genomic islands that also code for virulence factors. This functional and modular synergy confers a strong selective advantage for the domination of the colonic niche, which is the first step towards infection. This optimization of genetic resources might favor the selection of additional virulence factors, which are essential in the subsequent steps of pathogenesis in E. coli infection.